A network-individual-resource model for HIV prevention. - Johnson, Blair T; Redding, Colleen A; DiClemente, Ralph J; Mustanski, Brian S; Dodge, Brian; Sheeran, Paschal; Warren, Michelle R; Zimmerman, Rick S; Fisher, William A; Conner, Mark T; Carey, Michael P; Fisher, Jeffrey D; et al. (AIDS and behavior, 2010)
HIV is transmitted through dyadic exchanges of individuals linked in transitory or permanent networks of varying sizes. A theoretical perspective that bridges key individual level elements with important network elements can be a complementary foundation for developing and implementing HIV interventions with outcomes that are more sustainable over time and have greater dissemination potential. Toward that end, we introduce a Network-Individual-Resource (NIR) model for HIV prevention that recognizes how exchanges of resources between individuals and their networks underlies and sustains HIV-risk behaviors. Individual behavior change for HIV prevention, then, may be dependent on increasing the supportiveness of that individual's relevant networks for such change. Among other implications, an NIR model predicts that the success of prevention efforts depends on whether the prevention efforts (1) prompt behavior changes that can be sustained by the resources the individual or their networks possess; (2) meet individual and network needs and are consistent with the individual's current situation/developmental stage; (3) are trusted and valued; and (4) target high HIV-prevalence networks.
Keywords: Health Promotion; HIV Infections; Humans; Models, Psychological; Peer Group; Risk Reduction Behavior; Risk-Taking; Sexual Behavior; Social Environment; Social Support; Socioeconomic Factors; Stress, Psychological